Observation and Research on Seismic Response of Super High-rise Buildings. Issue 4 (May 2019) - Zhou, ChangXian; Zheng, ShaoPeng; Ye, YouQuan; Wang, Hao; Fu, Ping
Abstract: With the development of social economy, the increase of urban population and the shortage of land resources, the world has set off a high-rise building construction climax, More and more population concentrated and land-saving super-high-rise buildings are put into construction and use. However, the story height of this kind of building structure is higher, the layout of flat elevation is more complex, the experience of actual earthquake damage is lacking, and the seismic design is not sufficiently based, so the damage situation of this kind of building structure under earthquake is more complex than that of ordinary regular structure. This paper mainly studies the response of super high-rise buildings under seismic force, and briefly summarizes the research methods of seismic performance of such buildings.